Specific absorption rate intersubject variability in 7T parallel transmit MRI of the head. Issue 5 (3rd July 2012) - de Greef, Martijn; Ipek, Ozlem; Raaijmakers, Alexander J. E.; Crezee, Johannes; van den Berg, Cornelis A. T.
Abstract Patient‐specific radiofrequency shimming in high‐field MRI strengthens the need for online, patient‐specific specific absorption rate (SAR) monitoring. Numerical simulation is currently most effective for this purpose but may require a patient‐specific dielectric model. To investigate whether a generic model may be combined with a safety factor to account for variation within the population, generic SAR behavior is studied for 7T MRI of the head. For six detailed head models, radiofrequency fields were simulated for an eight‐channel parallel transmit array. SAR behavior is studied through comparison of the eigenvalues/eigenvectors of the local Q‐matrices. Furthermore, numerical radiofrequency shimming experiments without and with SAR constraints were performed where SAR during optimization was evaluated on a generic model. In both cases, the ability of different generic models to predict actual SAR levels was evaluated. The largest eigenvalue distribution is comparable between models. Radiofrequency shimming without constraints improves the |B +1<inline-graphic xlink:href="ark:/27927/pgg1xr49s9p" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />| homogeneity while the SAR increases substantially. Imposing constraints on SAR during optimization, estimating SAR on a generic model, was effective. A safety factor of 1.4 was found to be sufficient. Generic SAR behavior makes a generic head model a practical alternative to patient‐specific models and allows effective |B +1<inline-graphic xlink:href="ark:/27927/pgg1xr49sfw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />| shimming with SAR constraints. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.